Racism, slavery and social perspective on slavery in Oroonoko and Twelve Years A Slave - Nabila, Nazifa Farzana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.